New additions to the Honduran fauna of spider wasps (Hymenoptera: Pompilidae) with the description of two species - Waichert, Cecilia; Rodriguez, Juanita; Pitts, James P. (Zootaxa, 2014)
Two new species of pepsine spider wasps, Calopompilus setaerotundus Waichert & Pitts, sp. nov. and Priocnemis (Umbripennis) wasbaueri Waichert & Pitts, sp. nov., are described and illustrated. Calopompilus Ashmead, Priocnemis Schiødte and sixteen additional species are newly reported from Honduras. A new combination is proposed for Ageniella fragilis (Fox), comb. nov., which is transferred from Agenia Schiødte.